Noble gases in groundwater reflect wet-season temperature in an arid, monsoonal, and mountainous environment - Müller, Thomas; Rooij, Gerrit; Trauth, Nico; Schmidt, Mark; Badi, Humaid Al; Aeschbach, Werner (Earth and planetary science letters, 2024)
Comparing directly measured soil temperatures with noble gas recharge temperatures (NGTs) inferred from noble gas concentrations indicates that the infiltrating soil water equilibrates with soil air near the soil surface during the rainy season. Therefore, NGTs of groundwater recently recharged by the Indian Summer Monsoon (ISM) in the Dhofar Mountains in southern Oman reflect the soil temperatures of the 3-month period and do not represent an annual mean. This finding highlights the need to account for seasonality when interpreting NGT data in regions with pronounced dry and wet seasons. We extend the observations from the southern flank of the Dhofar Mountains to three wells situated on the northern flank of the Dhofar Mountains. Two of these wells yield water of Holocene age that was recharged by the monsoon, their NGT signals are therefore classified as seasonal. The NGT calculated from a third well for recharge conditions during the Last Glacial Maximum (LGM), when the ISM was absent, is approximately 3 °C lower than that of the two Holocene wells. The lower LGM noble gas temperature corresponds well with the lower annual Sea Surface Temperature (SST) in the nearby Arabian Sea. NGTs from published studies from northern Oman are 1-3 °C higher when compared with our data of the same period in the southern Oman. We explain this regional difference of reconstructed temperatures for the LGM and Holocene groundwater with a more continental climatic influence on the infiltration conditions further to the north. The published NGTs from northern Oman show a large temperature difference between the late Holocene and the LGM. In view of our finding of seasonal NGT signals under monsoonal climate, part of this difference may reflect a change in the precipitation regime rather than in air temperature.
Online verfügbar: 12. Dezember 2023
Gesehen am 13.03.2024